MENINGKATKAN KEMAMPUAN WRITING DENGAN PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK-PAIR-SHARE BERBANTUAN METODE PENUGASAN DAN RESITASI DENGAN KLIPING BERITA di SMP NEGERI 4 DENPASAR - Ni Made Aryawati (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2020)
This class action research aimed at finding out whether cooperative learning models Think-Pair-Share assisted with the assignment and recitation methods with news clippings is successful to improve the students achievement in writing skills. This research took a subject in class VII-6 SMP N 4 Denpasar at semester 2 academic year 2017/2018. The researcher has strived diligently so that the learning process can be carried out accordance with expectations, using the right strategies and adequate learning techniques.The result of the study were collected by learning achievement tests while the analysis used descriptive analysis. After all data is analyzed, it obtained an increase in learning outcomes from the beginning 67,11 with mastery learning 36,11%, increase in the first cycle to be 71,97 with mastery learning 72,22%. The result of the second cycle is 80,58 with the percentage of mastery learning has reached 100% and it has exceeded the criteria set for the research indicators. Based on the data obtained, the researcher concluded that cooperative leaning Think- Pair-Share through assignment and recitation methods with news clipping can improve the students writing skills in this school.